Efficacy and safety of an inactivated novel variant infectious bursal disease virus in broiler chickens - Hair-Bejo, Mohd; Gauthaman, Lathasha; Mazlan, Mazlina; Mohamed Sohaimi, Norfitriah; Clifford Ugwu, Chidozie (Scienceline Publication, 2024)
The infectious bursal disease virus (IBDV) is severe and highly contagious, causing high mortality and immunosuppression in chickens worldwide. A new novel variant, IBDV (nVarIBDV), has recently emerged in Asian countries, including Malaysia, highlighting the need to develop a new vaccine against this strain due to the inadequacy of existing commercial vaccines in protecting chickens from nVarIBDV infection. Therefore, the current study aimed to evaluate the efficacy and safety of inactivated nVarIBDV as a potential vaccine candidate in broiler chickens. A total of 65 one-day-old Arbo Acres broiler chickens were randomly divided into three groups (five animals in each group with four replications) before the challenge, namely A, B, and C. Groups A and B were immunized subcutaneously at day old with inactivated nVarIBDV (107 EID50/0.2 ml), and Group B was boosted at day 14. Group C was an unimmunized control. The experimental animals were divided into three subgroups and were challenged with pathogenic nVarIBDV (105 EID50/1.0ml) on day 28 post-inoculation through ocular and oral routes. The challenge sub-groups were named ACH, BCH, and CCH, respectively. The live body weight, bursa weight, and blood samples of the chickens were recorded. Gross lesions were examined, and samples of the bursa of Fabricius were collected from all the groups for histological evaluation. All the chickens appeared healthy and normal throughout the trial. Body weight increased in all groups without significant differences. The bursa weight and the bursa-to-body weight ratio of the booster group (Group B) were significantly higher than the non-booster and control groups. Gross lesions were not observed in the investigated groups. The challenged control group had higher bursa lesion scoring than the vaccinated groups. The IBDV antibody titer of challenged chickens in ACH, BCH, and CCH groups was higher than those of unchallenged groups A, B, and C at 35 days post-inoculation. The IBDV antibody titer of challenged chickens in group B was higher than challenged chickens in groups A and C (ACH and CCH). In conclusion, the inactivated nVarIBDV demonstrated safety and efficacy, with the booster Group (B) showing elevated humoral immune responses compared to the non-booster group. © The Author(s) 2024